2013
DOI: 10.1242/bio.20131065
|View full text |Cite
|
Sign up to set email alerts
|

TCTEX1D4, a novel protein phosphatase 1 interactor: connecting the phosphatase to the microtubule network

Abstract: SummaryReversible phosphorylation plays an important role as a mechanism of intracellular control in eukaryotes. PPP1, a major eukaryotic Ser/Thr-protein phosphatase, acquires its specificity by interacting with different protein regulators, also known as PPP1 interacting proteins (PIPs). In the present work we characterized a physiologically relevant PIP in testis. Using a yeast two-hybrid screen with a human testis cDNA library, we identified a novel PIP of PPP1CC2 isoform, the T-complex testis expressed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…TCTEX1D4 has already been described as a new PPP1 interacting protein [22]. This new interaction was supported by the yeast two-hybrid approach, co-immunoprecipitation and overlay techniques.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TCTEX1D4 has already been described as a new PPP1 interacting protein [22]. This new interaction was supported by the yeast two-hybrid approach, co-immunoprecipitation and overlay techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It was already shown that TCTEX1D4 interacts with membrane receptors, inhibiting TGFβ signaling [15] and suggesting its involvement in brain response to peripheral inflammation [21]. Previous results indicate that TCTEX1D4 is evolutionarily conserved among mammals and ubiquitously expressed, particularly in ovary, spleen, lung and placenta, where PPP1 is also present [22,23]. Moreover TCTEX1D4 interacts directly with PPP1C [22] and possesses a canonical PPP1 binding motif [5,8,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations